Networks and productivity: Causal evidence from editor rotations - Brogaard, Jonathan; Engelberg, Joseph; Parsons, Christopher A. (Journal of Financial Economics, 2014)
Using detailed publication and citation data for over 50,000 articles from 30 major economics and finance journals, we investigate whether network proximity to an editor influences research productivity. During an editor's tenure, his current university colleagues publish about 100% more papers in the editor's journal, compared to years when he is not editor. In contrast to editorial nepotism, such “inside” articles have significantly higher ex post citation counts, even when same-journal and self-cites are excluded. Our results thus suggest that despite potential conflicts of interest faced by editors, personal associations are used to improve selection decisions.